2022
DOI: 10.26480/mjg.02.2022.84.87
|View full text |Cite
|
Sign up to set email alerts
|

Application of Electrical Resistivity Tomography in Engineering Site Characterization: A Case Study of Igarra, Akoko Edo, Southwestern Nigeria

Abstract: To better understand the subsurface geological composition (relief, fault, fracture, discontinuities, orientation of structures) of the surrounding environment that anticipates infrastructural development in the near future due to population explosion, an Electrical Resistivity Tomography (ERT) survey was conducted in Igarra, Akoko Edo area of Edo state, Nigeria. The depth to bedrock, possible geologic structures (faults, fractures, voids) were some of the properties investigated. To determine the orientation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…The decision to show the geo-electric sections laterally demonstrates our dedication to provide a comprehensive understanding of the subsurface as well as a deeper comprehension of the spatial arrangement of resistivity and geophysical properties in the researched region (Falade et al, 2022;Pham et al, 2022). This technology's application has significant significance for geological and environmental research since it can aid in the development of a more accurate and comprehensive subsurface depiction.…”
Section: Results and Discussion Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The decision to show the geo-electric sections laterally demonstrates our dedication to provide a comprehensive understanding of the subsurface as well as a deeper comprehension of the spatial arrangement of resistivity and geophysical properties in the researched region (Falade et al, 2022;Pham et al, 2022). This technology's application has significant significance for geological and environmental research since it can aid in the development of a more accurate and comprehensive subsurface depiction.…”
Section: Results and Discussion Resultsmentioning
confidence: 99%
“…However, several studies have demonstrated the effectiveness of electrical resistivity tomography (ERT) in investigating subsurface geology and identifying buried structures (Gautier et al, 2023;Shamkhi & Karim, 2022). ERT has been used to detect and characterize sliding surfaces on landslides and active faults, as well as to investigate dynamic processes such as groundwater flows and soil moisture variations (Falade et al, 2022). Additionally, the use of electrical resistivity has shown promise in characterizing soil physical parameters, such as water content, dry unit weight, and clay fraction, which are important for understanding subsurface characteristics (Zamanian & Shahandashti, 2022).…”
Section: Introductionmentioning
confidence: 99%